Optimal artificial conditions for keeping and breeding medicinal leeches Hirudo verbana and Hirudo orientalis - Aminov, R.; Aminova, A.; Frolov, A.; Makyeyeva, L. V.; Макєєва, Людмила Валеріївна (My University, 2025)
The aim of the work is to obtain optimal artificial conditions for the maintenance and breeding of medicinal leeches of the species Hirudo verbana and Hirudo orientalis. 180 medicinal leeches were used in the study: 100 leeches of the H. verbana species and 80 H. orientalis leeches. Four groups of animals were formed: two control and two experimental. Control groups of medicinal leeches were kept using the standard jar method. Experiments according to the developed optimal scheme. As a result of the study, it was found that there were more juveniles obtained from the cocoon per 1 parent leech in the experimental group of medicinal leeches of the H. verbana and H. orientalis species, compared to the control group; appearance of defective cocoons. Mortality of parent leeches during breeding, mortality of juveniles before the first, after the first and sixth feeding decreases on average by more than 50% (P < 0.05) in the experimental group.
Keywords: medicinal leeches; optimal environment; breeding; keeping